Evaluation of over-the-counter medicines’ advertising in community pharmacies in the city of Niterói (RJ, Brazil) - Silva, Patricky Santos; Rangel, Brena da Costa Campos; Castilho, Selma Rodrigues de (Journal of Health Law, 2018)
Cross-sectional study for collection and analysis of the compliance with health legislation of OTC drug advertising, for consumers, available in pharmacies and private drugstores in the city of Niterói (Rio de Janeiro, Brazil). Of the 826 medicines' advertisements collected from 80 pharmacies, 379 were new. Approximately 99.5% of these pieces had some kind of irregularity according to the Brazilian Health Regulatory Agency Resolution n. 96/2008, averaging 5.1 offenses by piece analyzed, being 16 the maximum number of violations observed in a single piece. The results point to the risk imposed by the current landscape of drug advertising in the country to the population, daily exposed to this source of misinformation, and to the need for a more effective supervision of drug advertising that is directed to the lay public.